Early- and Late-Onset Preeclampsia at a Tertiary Hospital in 2016 - Hapsari Kinanti; Muhammad Ilham Aldika Akbar; Pudji Lestari (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2022)
Introduction: Preeclampsia is still one of the major causes of maternal morbidity and mortality worldwide. Preeclampsia nowadays has another classification, early-onset preeclampsia and late-onset preeclampsia. This study aimed to evaluate the differences between early-onset and late-onset preeclampsia in Dr. Soetomo General Hospital, Surabaya in 2016.Methods: This was an analytic observational study, evaluating the difference between early- and late-onset preeclampsia in terms of maternal data, medical history, and obstetric history. The samples were taken from the medical record of Dr. Soetomo General Hospital, Surabaya from January until December 2016.Results: In maternal data, early- and late-onset preeclampsia mostly happened in productive age, consisted of 34 patients of early-onset preeclampsia (77.3%) and 31 patients of late-onset preeclampsia (73.8%). Early-onset preeclampsia tended to happen in nullipara (42.2%) and primigravida (35.6%) women, and late-onset preeclampsia usually happened in multipara (43.9%) and multigravida (85.4%) women. In medical and obstetric history, early-onset preeclampsia mostly had a history of hypertension (61.7%), rather than late-onset preeclampsia (32.7%). Moreover, there were no significant differences in other variables.Conclusion: Early-onset and late-onset preeclampsia had a significant difference in parity, gravidity, and hypertension disease.